2022
DOI: 10.1111/acfi.13028
|View full text |Cite
|
Sign up to set email alerts
|

Non‐GAAP earnings reporting following going‐concern opinions

Abstract: We examine non‐GAAP earnings reporting following a going‐concern audit opinion (GCO). Using a propensity score‐matched sample, matching first‐time going‐concern issuing companies with firms in financial distress that did not receive a going‐concern report, we find that the likelihood and frequency of non‐GAAP earnings reporting are lower following GCOs. In additional analyses, we find the negative association between the announcement of GCOs and the likelihood and frequency of non‐GAAP earnings reporting stron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…Non-GAAP earnings are more informative than non-recurring gains and losses (Wang, 2017). Zhang et al (2022) showed that the likelihood and frequency of non-GAAP earnings reporting are lower following a goingconcern audit opinion (GCO). Young (2014) reviewed the academic and professional debate surrounding non-GAAP earnings reporting by management, arguing that the demand for customized performance reporting is a natural response to constraints imposed by a one-size-fits-all reporting system and that the non-GAAP phenomenon is part of a long-standing debate over the definition and presentation of periodic performance and his work was further discussed by Miller (2014).…”
Section: Introductionmentioning
confidence: 99%
“…Non-GAAP earnings are more informative than non-recurring gains and losses (Wang, 2017). Zhang et al (2022) showed that the likelihood and frequency of non-GAAP earnings reporting are lower following a goingconcern audit opinion (GCO). Young (2014) reviewed the academic and professional debate surrounding non-GAAP earnings reporting by management, arguing that the demand for customized performance reporting is a natural response to constraints imposed by a one-size-fits-all reporting system and that the non-GAAP phenomenon is part of a long-standing debate over the definition and presentation of periodic performance and his work was further discussed by Miller (2014).…”
Section: Introductionmentioning
confidence: 99%